Pengembangan Sistem Informasi Layanan Asesmen Minat Karir di Unisba Career Development Center (UCDC) - 10070216117, Rivaldi Fasry Marcellino Tallei; Djamaludin (Bandung Conference Series: Industrial Engineering Science, 2024)
Abstract. Unisba Career Development Center or UCDC is the development of a career center for Unisba students and alumni whose aim is to provide information on the world of work, assessment services and career counseling. The assessment method carried out by UCDC is still manual, so a career interest assessment service is needed using technological information so that it is easily accessible to students and alumni. This final project research uses the Rapid Application Development (RAD) method because it is suitable for developing information systems that are needed quickly and focuses on company input in new information planning systems. This method consists of three stages, namely requirements planning which defines system requirements, system design which represents the design system based on company needs, and implementation which transforms the design results into products. The system development that has been carried out provides all the features needed by UCDC, such as career interest assessment instruments, interpretation of career interest results, and job recommendations based on personality types that are suitable for the work environment. Based on the implementation results, it is known that all system functional requirements have been met, which means the system can solve the UCDC problem. The conclusion drawn is that the career interest assessment service information system helps students and alumni to identify and indicate their interest in conservation through the use of information technology. However, further evaluation and development needs to be carried out to increase the relevance of information systems to the ever-changing needs of users. Abstrak. Unisba Career Development Center atau UCDC adalah pusat pengembangan karir bagi mahasiswa dan alumni Unisba yang memiliki tujuan untuk memberikan informasi dunia kerja, layanan asesmen dan konseling karir. Metode asesmen yang dilakukan oleh UCDC masih manual sehingga diperlukannya layanan asesmen minat karir dengan pemanfaatan teknologi informasi sehingga mudah diakses oleh mahasiswa maupun alumni. Penelitian Tugas Akhir ini menggunakan metode Rapid Application Development (RAD) karena cocok dengan pengembangan sistem informasi yang dibutuhkan secara cepat dan berorientasi pada masukan perusahaan dalam perencanaan sistem informasi yang baru. Metode ini terdiri dari tiga tahap yaitu perencanaan kebutuhan yang mendefinisikan persyaratan sistem, desain sistem yang merepresentasikan rancangan sistem berdasarkan kebutuhan perusahaan, dan implementasi yang mentransformasi hasil rancangan menjadi produk. Pengembangan sistem yang telah dilakukan menyediakan semua fitur yang dibutuhkan UCDC seperti instrumen asesmen minat karir, interpretasi hasil minat karir, serta rekomendasi pekerjaan berdasarkan tipe kepribadian yang cocok dengan lingkungan kerja. Berdasarkan hasil implementasi diketahui bahwa seluruh kebutuhan fungsional sistem sudah terpenuhi yang artinya sistem dapat menyelesaikan permasalahan UCDC. Kesimpulan yang ditarik yaitu sistem informasi layanan asesmen minat karir membantu mahasiswa dan alumni untuk mengetahui dan memetakan minat karirnya melalui pemanfaatan teknologi informasi. Namun, perlu dilakukan evaluasi dan pengembangan lebih lanjut untuk meningkatkan relevansi sistem informasi dengan kebutuhan pengguna yang selalu berubah.